2020
DOI: 10.3390/ma13143127
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Reinforced Concrete Beam with Openings Strengthened Using FRP Sheets under Cyclic Load

Abstract: In this study, the cyclic behavior of reinforced concrete (RC) beam with openings strengthened using carbon fiber-reinforced polymers (FRPs) was experimentally investigated. Seven rectangular RC beams were cast and strengthened through external bonding of carbon fiber-reinforced polymer (CFRP) sheets around the beam web opening with different orientations to evaluate the maximum resistance, secant stiffness, strength degradation, ductility, energy dissipation capacity and behavior of the specimens’ failure mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
0
24
0
2
Order By: Relevance
“…the same failure mode of the control beam without a web opening, as shown in Figure 2(b)] (e.g. Abdalla et al, 2003; Aksoylu et al, 2020; Mansur et al, 1999; Pimanmas, 2010; Salih et al, 2020); however, if the FRP-strengthening is insufficient and the shear capacities of the cross-sections in the opening region cannot be restored (i.e. smaller than the flexural capacities of the cross-sections), the beam will still fail by shear in the opening region after the debonding/rupture of FRP.…”
Section: Existing Experimental Studiesmentioning
confidence: 83%
See 2 more Smart Citations
“…the same failure mode of the control beam without a web opening, as shown in Figure 2(b)] (e.g. Abdalla et al, 2003; Aksoylu et al, 2020; Mansur et al, 1999; Pimanmas, 2010; Salih et al, 2020); however, if the FRP-strengthening is insufficient and the shear capacities of the cross-sections in the opening region cannot be restored (i.e. smaller than the flexural capacities of the cross-sections), the beam will still fail by shear in the opening region after the debonding/rupture of FRP.…”
Section: Existing Experimental Studiesmentioning
confidence: 83%
“…A total of 24 experimental studies on the behaviour of RC beams with an FRP-strengthened web opening have been found in the published literature (Abdalla et al, 2003; Abdel-Kareem 2014; Aksoylu et al, 2020; Allam, 2005; Allawi et al, 2020; Almusallam et al, 2018; Arabzadeh and Karimizadeh, 2019; Chin et al, 2012, 2016; Elsanadedy et al, 2019; Hemzah et al, 2020; Hussain and Pimanmas, 2015; Lu et al, 2015; Maaddawy and Ariss, 2012; Maaddawy and Sherif, 2009; Makki et al, 2019; Mansur et al, 1999; Nie et al, 2018, 2020a; Osman et al, 2017b; Pimanmas, 2010; Rahim et al, 2020; Salih et al, 2020; Teng et al, 2013b). The first of these studies was conducted by Mansur et al (1999), in which three RC T-section beams were tested with only one parameter examined (i.e.…”
Section: Existing Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otra parte, las láminas de PRFC tienen un efecto significativo en el comportamiento cíclico de las vigas de CA, mejorando así la resistencia máxima y el desplazamiento último hasta aproximadamente el 66.67% y el 77.14% en vigas [47] .…”
Section: Losas Con Prfcunclassified
“…Test results confirmed validity of the numerical study. Salih et al [25] investigated both experimental and numerical behaviour of RC beams whose openings were strengthened using CFRP. FE results were verified by experiments.…”
Section: Introductionmentioning
confidence: 99%